2018
DOI: 10.1080/09537104.2018.1453059
|View full text |Cite
|
Sign up to set email alerts
|

The pro-inflammatory role of platelets in cancer

Abstract: Thrombosis is a frequent issue in cancer patients. Tumor-induced platelet activation and coagulation does not only constitute a significant risk for thrombosis, but also contribute to tumor progression by promoting critical processes such as angiogenesis and metastasis. In addition to their role in hemostasis, platelets are increasingly recognized as regulators of inflammation. By modulating the immune system, platelets regulate several aspects of cancer-associated pathology. Platelets influence the inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 73 publications
(77 reference statements)
0
96
0
1
Order By: Relevance
“…The literature also supports the association of elevated platelet counts with lung cancer risk 59 . Still it is plausible that thrombocytes could contribute to tumor progression by stimulating angiogenesis 67 and activating thrombosis-related inflammation 68 . In addition, observational studies have found that the composition of blood cells including neutrophil-lymphocyte ratio and thrombocyte-lymphocyte ratio are associated with overall and disease-free survival in multiple cancers 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature also supports the association of elevated platelet counts with lung cancer risk 59 . Still it is plausible that thrombocytes could contribute to tumor progression by stimulating angiogenesis 67 and activating thrombosis-related inflammation 68 . In addition, observational studies have found that the composition of blood cells including neutrophil-lymphocyte ratio and thrombocyte-lymphocyte ratio are associated with overall and disease-free survival in multiple cancers 69 .…”
Section: Discussionmentioning
confidence: 99%
“…ANC, as a measure of systemic inflammatory response to malignancy, is linked to immunosuppression in certain tumors . Furthermore, platelets can be stimulated by systemic inflammation through several pro‐inflammatory factors, such as IL‐1, IL‐3, and IL‐6, and platelet aggregation and degranulation leads to the release of platelet‐derived proangiogenic mediators, which have been suggested to promote tumor growth .…”
Section: Discussionmentioning
confidence: 99%
“…Various types of tumor cells and tumor-derived ECs can activate platelets by different mechanisms. There is plenty of evidence that activated platelets exert their pleiotropic effects on many biological processes central to angiogenesis, progression, inflammation and metastasis in various tumor types [57,60,61]. Improving our understanding of such platelet involvement in neovascularization may potentially help in the development of alternative treatment strategies for patients with KHE.…”
Section: Platelet Aggregation: a Key Trigger Of Kmp?mentioning
confidence: 99%